(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2018)
History contributes in an essential way to the formation of a nation’s self-perception and identity and the education system is a key mechanism by which this knowledge is dispersed. It is therefore of great concern that students in both Australia and Germany consistently report being bored when learning of their respective nation’s fraught history. This essay analyses the shortcomings of Australia’s Indigenous history education in comparison with Germany’s Holocaust education, examining via psychoanalytic theory how the phenomenon of boredom often acts to suppress difficult feelings such as guilt. Keywords Aboriginal history; genocide studies; history wars